Global surveillance of emerging diseases: the ProMED-mail perspective - John P. Woodall
The Internet is changing the way global disease surveillance is conducted. Countries and international organizations are increasingly placing their outbreak reports on the Internet, which speeds up distribution and therefore prevention and control. The World Health Organization (WHO) has recognized the value of nongovernmental organizations and the media in reporting outbreaks, which it then attempts to verify through its country offices. However, WHO and other official sources are constrained in their reporting by the need for bureaucratic clearance. ProMED-mail <www.promedmail.org> has no such constraints, and posts outbreak reports 7 days a week. It is moderated by infectious disease specialists who add relevant comments. Thus, ProMED-mail complements official sources and provides early warning of outbreaks. Its network is more than 20,000 people in over 150 countries, who place their computers and time at the network's disposal and report on outbreaks of which they have knowledge. Regions and countries could benefit from adopting the ProMED-mail approach to complement their own disease surveillance systems.